2020
DOI: 10.3390/ijerph17207679
|View full text |Cite
|
Sign up to set email alerts
|

mHealth and Perinatal Depression in Low-and Middle-Income Countries: A Scoping Review of the Literature

Abstract: Women in low- and middle-income countries have high rates of perinatal depression. As smartphones become increasingly accessible around the world, there is an opportunity to explore innovative mHealth tools for the prevention, screening, and management of perinatal depression. We completed a scoping review of the literature pertaining to the use of mobile phone technologies for perinatal depression in low-and middle-income countries. PubMed CINHAL, and Google Scholar databases were searched, generating 423 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Moreover, Women in their perinatal period are more prone to depression because of pregnancy-related issues. 5 Acknowledging maternal psychological well-being will likely benefit these vital outcomes. The earlier these conditions are acknowledged and addressed, the greater the likelihood of reducing their impact.…”
Section: Research Gapmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Women in their perinatal period are more prone to depression because of pregnancy-related issues. 5 Acknowledging maternal psychological well-being will likely benefit these vital outcomes. The earlier these conditions are acknowledged and addressed, the greater the likelihood of reducing their impact.…”
Section: Research Gapmentioning
confidence: 99%
“…4 The mental health of pregnant women in low-and middle-income countries is more worrisome. 5 Furthermore, the occurrence of mental health problems during pregnancy is significantly higher in the postnatal period. 6 Therefore, attention should be given to the mental health of women during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrating potential end-users in the development process of digital technologies has resulted in engaging products that prevent inequities in digital health technology use [7]. However, research on how best to leverage digital technologies to reduce disparities in PPD literacy and access to care is scarce [8]. Thus, the purpose of this study is to contribute to existing knowledge by characterizing the information and socio-technical needs of low-SES peripartum women in high-risk pregnancies to formulate and engineer responsive digital technologies for the underserved communities that are plagued with health disparities.…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses showed that Web-based and Mobile-based psychological interventions are effective to prevent depression in the general population ( Rigabert et al, 2020 ; Deady et al, 2017 ; Stratton et al, 2017 ; Sander et al, 2016 ), but the evidence is scarce concerning the prevention of perinatal depression. To date, eight systematic reviews aimed at overviewing Web-based and Mobile-based interventions during the perinatal period ( Dosani et al, 2020 ; Hussain-Shamsy et al, 2020 ; Roman et al, 2020 ; Zhou et al, 2020 ; Ashford et al, 2016 ; Lau et al, 2017 ; Van Den Heuvel et al, 2018 ; Loughnan et al, 2019 ; Lee et al, 2016 ) have been published. However, their focus was not on prevention studies (studies on treatment interventions are also included); all types of interventions were included (such as healthy lifestyles and smoking cessation) and were restricted to the postpartum period.…”
Section: Introductionmentioning
confidence: 99%